Physical Quality of Gelatin Edible Film with Addition of Oleogel - Dafista, Dela; Putriwahyuningtyas, Eka; Khairinnisa, Faaliha Rahma; Wiryawan, Dimas; Saleha, Rischa Amalia; Apriliyani, Mulia Winirsya; Manab, Abdul (Faculty of Animal Science Universitas Brawijaya, 2026)
The growing problem of microplastic contamination has prompted the need for safer and more environmentally friendly food packaging alternatives. An edible film made from gelatin with the addition of chitosan, sorbitol, TiO?, and oleogel has been developed to replace conventional plastic, which is difficult to decompose. This study aims to determine the physical properties of gelatin with oleogel-based edible film in terms of the physical and mechanical properties of edible films. Treatment: the use of different oleogel (0%, 3%, 6% and 9%) with 4 replications. The method used was an experimental method using a Completely Randomized Design (CRD). The observed variables were Water Vapor Permeability (WVP), solubility, thickness and transparency. The parameters observed included swelling, moisture content, color intensity (L*, a*, b*), tensile strength, elongation at break. Data were analyzed using Analysis of Variance (ANOVA). The results of the study using oleogel with different percentage show highly significant differences (p < 0.01) on wvp, solubility, thickness, transparency, swelling, moisture content, color, breaking strength and tensile strength, but did not show significant differences (p > 0.05) on a* value. The results showed that the addition of oleogel reduced moisture content, swelling, L* values, solubility, wvp and breaking strength but increased a* value, b* values, tensile strength, thickness and transparency. Based on these results, the use of oleogel in edible films can enhance physical and mechanical properties of edible films, thereby potentially serving as an environmentally friendly alternative for food packaging